The Role of Suprasegmental Features in English Phonology: Prosodic Hierarchy and Intonation Patterns - Nabila Zuhairya; Puspita Maharani; Achmad Ridwan; Khairunnisa Khairunnisa; Sahfitri Ahwani; Yani Lubis (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study explores the significance of suprasegmental features in English phonology, focusing on prosodic hierarchy and intonation patterns. The analysis delves into how these features play a crucial role in structuring spoken language, particularly in conveying nuances, emotions, and pragmatic information. The study highlights the importance of understanding suprasegmental features in enhancing speaking proficiency in English and their relevance to English language curriculum development. Further research opportunities in English phonology, such as investigating other suprasegmental features and adopting an interdisciplinary approach, are suggested to deepen the understanding of English phonological structures and improve the quality of teaching speaking skills in English. This study emphasizes the valuable insights gained from a deeper understanding of the role of suprasegmental features in English phonology for teaching, research, and overall understanding of oral language